Sequence specific interaction of the chromosomal proteins with DNA. - Tuan, D (1977)
Calf thymus chromatin was partially deproteinized by 0.6-1 M NaCl extraction. From the shape of the temperature derivative plot of its melting curve, the DNA in each chromatin was resolved into regions of exposed DNA, and DNA still complexed with proteins. The partially deproteinized chromatin was capable of directing in vitro RNA synthesis in an amount proportional to the fraction of exposed DNA. The in vitro RNA transcript was hybridized to denatured calf DNA under hybridization conditions where only RNA's transcribed from repetitive DNA sequences were able to form hybrids. From the results it is deduced that the in vitro RNA transcripts of 0.6 M NaC1-extracted chromatin after the removal of HI histones plus one-quater of the non histones may be transcribed from repetitive DNA sequences and those of 1 M NaCl-extracted chromatin contain more transcripts from the unique DNA sequences.